$ax + by + c = 0$ is the polar of $\left( {1,1} \right)$ with respect to the circle ${x^2} + {y^2} - 2x + 2y + 1 = 0$ and HCF of $a,b,c$ is equal to $1$, then find ${a^2} + {b^2} + {c^2}$.
A) $0$
B) $3$
C) $5$
D) $15$
Answer
Verified
482.4k+ views
Hint: If ${x^2} + {y^2} - 2x + 2y + 1 = 0$ is the equation and we need to write the equation of polar of $\left( {{x_1},{y_1}} \right)$ with respect to this ${x^2} + {y^2} - 2x + 2y + 1 = 0$ is given as
$x{x_1} + y{y_1} - 2\left( {\dfrac{{x + {x_1}}}{2}} \right) + 2\left( {\dfrac{{y + {y_1}}}{2}} \right) = 0$ .
Complete step-by-step answer:
So question is saying that $ax + by + c = 0$ is the polar of $\left( {1,1} \right)$ with respect to the circle ${x^2} + {y^2} - 2x + 2y + 1 = 0$. So we know in polar form, we replace ${x^2}$ by $x{x_1}$, ${y^2}$ by $y{y_1}$,
$x$ by $\dfrac{{x + {x_1}}}{2}$ and $y$ by $\dfrac{{y + {y_1}}}{2}$
So, polar of $\left( {1,1} \right)$ with respect to the circle ${x^2} + {y^2} - 2x + 2y + 1 = 0$ is
$x{x_1} + y{y_1} - 2\left( {\dfrac{{x + {x_1}}}{2}} \right) + 2\left( {\dfrac{{y + {y_1}}}{2}} \right) = 0$
And here, $\left( {{x_1},{y_1}} \right) = \left( {1,1} \right)$
So putting ${x_1} = 1,{y_1} = 1$ we will get the equation.
$
x + y - \left( {x + 1} \right) + \left( {y + 1} \right) + 1 = 0 \\
2y + 1 = 0 \\
$
Here the equation of polar of $\left( {1,1} \right)$ with respect to the circle is given by
$2y + 1 = 0$
But it is given that $ax + by + c = 0$ is the polar of $\left( {1,1} \right)$ with respect to the circle.
So upon comparing equations $2y + 1 = 0$ and $ax + by + c = 0$
We get
$\dfrac{a}{0} = \dfrac{b}{2} = \dfrac{c}{1}$
So,
$b = 2,c = 1,a = 0$
As it is given that HCF of $a,b,c$ is equal to $1$, so, we found the values of $a,b,c$ that are equal to $0,2,1$ respectively.
Now according to question, it is asked to find ${a^2} + {b^2} + {c^2}$
$
= {0^2} + {2^2} + {1^2} \\
= 0 + 4 + 1 \\
= 5 \\
$
Hence option C is correct.
Note: We should know how to convert equation in polar of $\left( {{x_1},{y_1}} \right)$ just make some changes as follows:
replace ${x^2}$ by $x{x_1}$, ${y^2}$ by $y{y_1}$,
$x$ by $\dfrac{{x + {x_1}}}{2}$ and $y$ by $\dfrac{{y + {y_1}}}{2}$ and constant remains same.
HCF is one means its highest common factor will always be one.
$x{x_1} + y{y_1} - 2\left( {\dfrac{{x + {x_1}}}{2}} \right) + 2\left( {\dfrac{{y + {y_1}}}{2}} \right) = 0$ .
Complete step-by-step answer:
So question is saying that $ax + by + c = 0$ is the polar of $\left( {1,1} \right)$ with respect to the circle ${x^2} + {y^2} - 2x + 2y + 1 = 0$. So we know in polar form, we replace ${x^2}$ by $x{x_1}$, ${y^2}$ by $y{y_1}$,
$x$ by $\dfrac{{x + {x_1}}}{2}$ and $y$ by $\dfrac{{y + {y_1}}}{2}$
So, polar of $\left( {1,1} \right)$ with respect to the circle ${x^2} + {y^2} - 2x + 2y + 1 = 0$ is
$x{x_1} + y{y_1} - 2\left( {\dfrac{{x + {x_1}}}{2}} \right) + 2\left( {\dfrac{{y + {y_1}}}{2}} \right) = 0$
And here, $\left( {{x_1},{y_1}} \right) = \left( {1,1} \right)$
So putting ${x_1} = 1,{y_1} = 1$ we will get the equation.
$
x + y - \left( {x + 1} \right) + \left( {y + 1} \right) + 1 = 0 \\
2y + 1 = 0 \\
$
Here the equation of polar of $\left( {1,1} \right)$ with respect to the circle is given by
$2y + 1 = 0$
But it is given that $ax + by + c = 0$ is the polar of $\left( {1,1} \right)$ with respect to the circle.
So upon comparing equations $2y + 1 = 0$ and $ax + by + c = 0$
We get
$\dfrac{a}{0} = \dfrac{b}{2} = \dfrac{c}{1}$
So,
$b = 2,c = 1,a = 0$
As it is given that HCF of $a,b,c$ is equal to $1$, so, we found the values of $a,b,c$ that are equal to $0,2,1$ respectively.
Now according to question, it is asked to find ${a^2} + {b^2} + {c^2}$
$
= {0^2} + {2^2} + {1^2} \\
= 0 + 4 + 1 \\
= 5 \\
$
Hence option C is correct.
Note: We should know how to convert equation in polar of $\left( {{x_1},{y_1}} \right)$ just make some changes as follows:
replace ${x^2}$ by $x{x_1}$, ${y^2}$ by $y{y_1}$,
$x$ by $\dfrac{{x + {x_1}}}{2}$ and $y$ by $\dfrac{{y + {y_1}}}{2}$ and constant remains same.
HCF is one means its highest common factor will always be one.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE